Self-perception of abilities emerging digital in the management of computer tools - Diaz Vera, Janeth Pilar; Ruiz Ramírez, Alicia Karina; Magallán Jiménez, Fernando Santana; Orozco Lara, Fausto Raúl (Revista Universidad de Guayaquil, 2023)
This research deals with the digital skills that students of the Faculty of Mathematical Sciences and Physics of the University of Guayaquil have for the proper management of computer tools. As a general objective, it was proposed to analyze the self-perception of emerging digital skills in the proper handling of computer tools in computer science undergraduate students in the learning process. For the development of this research, an exploratory research with a documentary design that used the secondary bibliographic review was considered as an approach and as a method of data collection, a survey of 357 students to whom a questionnaire developed by the students was applied as an instrument. authors (Organista-Sandoval, Gilles, Serrano-Santoyo, & Sandoval-Silva, 2019), to estimate the digital skills that students have to handle computer tools, and which is based on four dimensions: computer science, effective and collaborative communication, coexistence digital and technological From the results obtained, it is concluded that the student body presents an expected level of achievement in areas of digital dimensions due to the fact that they are immersed in the constant use of technologies, which is why they have developed various digital skills and mostly in a autonomous, which must be considered by the teaching staff so that they make decisions to improve the teaching-learning process based on technology, since if the teaching staff presents desirable digital competences, they would allow strengthening and developing the digital competences that students require in their professional training.
Keywords: Digital skills; computer tools; online classes; management